Workplace Wellness Programs Study Final Report - Mattke, Soeren (RAND Corporation, 2013)
The report investigates the characteristics of workplace wellness programs, their prevalence and impact on employee health and medical cost, facilitators of their success, and the role of incentives in such programs. The authors employ four data collection and analysis streams: a literature review, a survey of employers, a longitudinal analysis of medical claims and wellness program data from a sample of employers, and five employer case studies.